Analisa Pengaruh Perbandingan Debit Bahan Bakar Gas Dengan Udara Pembakaran Terhadap Efisiensi Boiler Di PT. Chevron Pacific Indonesia - Derry Hanriansyah Pratama; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Boiler is an equipment to generate steam. Steam has heat value in which used for some process. In this case, steam has been used for liftingoil from reservoir as an enhanced oil recovery. Operate boiler efficiently is a must. Operate boiler more efficiently can be achieved by fuel gas and air combustion adjustment. The objectives of this research are to know influences of excess oxygen for boiler efficiency and to know right composition between fuel gas and air combustion. Fix variables in this research are feed water flow (110 GPM) and heat value of fuel gas (1,000 BTU/scf). Fuel gas flow and air combustion flow are the adjustable variable. Fuel gas flow was adjusted in 5 flow variances (1050, 1070, 1090, 1110, and 1130 MSCFD). Air combustion flow was adjusted in 5 flow variances (70, 75, 80, 85, and 90% of louver opening). According to analysis results, the most efficient of boiler operation was 81.55%. That was achieved by 1050 MSCFD of fuel gas flow and 70% of air combustion flow. Boiler efficiency will decrease 2% in every 1% of excess oxygen increase.Keyword: boiler, steam, combustion, efficiency.